WORK STRESS AS A MEDIATOR OF JOB DEMAND ON TURNOVER INTENTION - Sylvia Diana Purba; Helena Winata; Efendi Efendi (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2019)
High job demand can be a factor that increases work stress and decreases job satisfaction, that it is expected to increases employee turnover intention. This research conducted on 50 employees from a department store. The purpose of this study is to examine mediation of work stress and job satisfaction on the influence of job demand toward the employee’s turnover intention. The result of this study cannot prove significantly the influence job demand toward turnover intention through the mediation effect of work stress. Job satisfaction can mediate the influence of job demand towards turnover intention. Other results found in this study show that there is an influence of job demand on turnover intention through the mediation of work stress and job satisfaction.